The effects of early weaning on Pavlovian fear conditioning in young rats - Kreiker, Malaz; Perez, Katelyn; Brown, Kevin L. (Developmental psychobiology, 2021)
Early life stress enhances memory for Pavlovian fear conditioning. Stress enhancements on fear conditioning following early weaning, however, have yet to be studied in periweaning rats. Early weaning is a relevant animal model for human early life trauma, and Pavlovian fear conditioning is useful for identifying links between stress‐induced developmental changes and behavior. We hypothesized that early weaning—on postnatal day (P)15—would lead to higher levels of conditional freezing relative to rats weaned later in life. Periweaning rats were trained with a discrete conditional stimulus (CS) and a shock unconditional stimulus (US), and tested 1 or 15 days later. Enhanced retention was observed in early weaned rats receiving forward paired CS–US training in Experiment 1, though this did not replicate in the second experiment. Despite overall enhancements in early weaned rats in Experiment 1, infantile amnesia effects were not overcome in young rats tested 15 days after training. Enhanced freezing levels in early weaned rats were not observed in subjects receiving unpaired CS, US training, and sensitivity to the US was not different due to age at weaning. Potential mechanisms underlying weaning‐related enhancements and considerations for future studies including the role of social transmission of fear information are discussed.